Influence of Urban Settlements’ Geometry on Outdoor Thermal Conditions and Comfort: A Case Study of Kampung in Surabaya-Indonesia - Ronalmanto Ronalmanto; I Gusti Ngurah Antaryama; Sri Nastiti Nugrahani Ekasiwi (Institut Teknologi Sepuluh Nopember, 2020)
In urban areas, especially urban settlements, low thermal comfort at pedestrian height and the high use of building energy are two interrelated conditions. Geometry of built environment is a factor that correlates with thermal conditions of the location and comfort. Understanding how geometry of built environment affects conditions and thermal comfort can be the basis for improving thermal condition as well as increasing thermal comfort. This study examines the influence of urban settlement geometry to thermal conditions and thermal comfort of urban space. An experiment was carried out on ten blocks, consisting of two block models and two orientations: Blocks with Different Height-to-Width Ratio (H / W = 0.8-1.5-2.3) and Blocks with the Same Height-to-Width Ratio but With Different Left-Right Height (H / W = 1.5-1.5'-1.5